TEORI GINZBERG EFEKTIVITAS LAYANAN BIMBINGAN KARIR TEORI GINZBERG DALAM MENINGKATKAN MINAT STUDI LANJUT PERGURUAN TINGGI - Uke, Ora Gorez; Jawawi, M. Abdurrohim; inaifas, Aminullah (Universitas Al-Falah As-Sunniyah Kencong Jember, 2021)
Career guidance is one of the duties of counseling guidance services. Career guidance functions to assist students in planning their careers after graduating from educational institutions. Further study in higher education is one of the career options that students can choose after graduating from high school. Ginzberg's theory is a career guidance theory that can be applied to develop students' career interests. Ginzberg's theory suggests that there are four factors that influence a person's choice of career, these four factors are reality, education, emotional and personal values. The focus of the problem in this study is whether Ginzberg's theory of career guidance services is effective in increasing interest in further tertiary studies at State Senior High School 1 Kencong. The purpose of this study was to find out whether Ginzberg's theory of career guidance services can influence interest in further tertiary studies at State Senior High School 1 Kencong. This study uses quantitative methods, while the type of research is one group pretest-posttest design, namely experimental research carried out in one group. The primary data sources in this study are the results of the pretest and posttest of the research object. The secondary sources are literature that supports research such as journals, books and others. The data collection technique used was to distribute questionnaires and the data analysis technique used was paired sample t-test analysis with the help of SPSS 25. The results of the analysis were: t count 13,796 > t table 2,001 and sig (2-tailed) values. 0.000, the sig 2 tailed value is 0.000 <0.05 which means Ho is rejected. This study concluded that Ha was accepted, meaning that the career guidance service of Ginzberg's theory was effective in increasing the interest in further studies of the students of State Senior High School 1 Kencong. Career guidance services based on Ginzberg's theory can be provided to students to help them gain understanding and direction in the process of preparing themselves to take college further studies.